Pengaruh Kelelahan Kerja dan Stres Kerja terhadap Kinerja Karyawan melalui Efikasi Diri pada Pekerja Film di Indonesia - Marikar, Cynthia Hidayat; Shaleh, Abdul Rahman (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Watching films is an essential part of human recreational needs that becomes increasingly pressing with age and changing requirements. With advancements in technology, watching films has become a primary necessity due to easy accessibility and the availability of streaming platforms. This study aims to explore the effects of work fatigue, work stress, and self-efficacy on employee performance in the film industry. The research population consists of film workers at PT. MD Pictures, with samples taken using purposive sampling methods. Data were analyzed using Path Analysis with the aid of JASP 19.0 software. The tests employed in this research include construct validity tests, path coefficient analysis, and hypothesis testing. The results indicate that self-efficacy significantly mediates the effect of work stress on the performance of film crews (t = 5.590, p < 0.001), but this does not hold for work fatigue (t = -0.120, p = 0.904). Work fatigue has a significant direct effect on performance (t = 2.733, p = 0.006), while its indirect effect through self-efficacy is not significant (t = -0.120, p = 0.904). Conversely, work stress does not have a significant direct effect on performance (t = 0.318, p = 0.751), but its indirect effect through self-efficacy is significant (t = 5.590, p < 0.001). Overall, the direct effect of work fatigue on performance is greater than its indirect effect, while for work stress, the indirect effect through self-efficacy is more significant than the direct effect. This research model shows that 88.7% of the variability in film crew performance can be explained by work fatigue, work stress, and self-efficacy, with an R² value of 0.887. Additionally, 40.3% of the variability in self-efficacy can be explained by work fatigue and work stress, as indicated by an R² value of 0.403. These findings suggest that improving self-efficacy can help mitigate the negative impact of work stress on the performance of film crews. However, in cases of work fatigue, direct intervention to address fatigue is more necessary than enhancing self-efficacy.